(untitled) (Archaeologia Adriatica, 2009)
A limestone stele from the village of Lobor (north-western Croatia) was accidentally recovered in 1857, but its archaeological context has never been established (figs. 1, 2). Its find spot belonged to a Roman settlement or a villa in the territory of either Andautonia or Poetovio, both towns in the Roman province of Pannonia Superior. It was first published in 1909, the stress being on epigraphy, and was later mentioned in passing in a number of articles in various contexts. In some of them the stele in question was illustrated by drawings featuring some false or imprecise details (figs. 3, 4); therefore, a new one has been made for the needs of the present discussion (fig. 2). The aim of this paper was to discuss the stone from Lobor in detail, with the stress on military iconography, social context of its use and the workshop affiliation. The epitaph reveals that the tombstone was put up by the mother and a brother, Septimia Lucilla and Cocceius, signifer of Legio X gemina, to 30-year-old Marcus Cocceius Superianus, centurion of the same legion and to 40-year-old praetorian Valerius Lucilianus. It transpires from the names and the woman’s clothes that it was an early Romanised native family, with a long tradition of serving in the Roman army. The dress and equipment of both soldiers are the same: a sagum with a round brooch, a long-sleeve tunic, a belt with a rectangular frame buckle, a spatha worn on the left side and ending in a round scabbard chape and a baldric featuring an oval mount. The only difference between them is in that the soldier on the right side has one scroll in his left hand, while the other one has two, one each in each hand (possibly the praetorian). The woman is clad in native costume, with the overdress fastened on the shoulders by brooches of the shape unparalleled elsewhere. On the basis of the dress, equipment and the portraits, the stele should be dated 220-250 A.D. The form of the stone points toward Norican typological traits and seems to have been manufactured in the workshop(s) of Andautonia or under its influence, rather than in Poetovio. A comparison between the stele from Lobor and one from Brusnik (mid northern Croatia) (fig. 5), whose typology is completely different although it was also military (legionary) and from the same period and the same province, points to soldiers as an integrated element of the civilian community.